Twelfth Finance Commission: farming its terms of reference - Vithal, B.P.R.; Sarma, J.V.M. (2002)
Considerations of making the recommendations of the Twelfth Finance Commission more effective require the new commission to (1) remove the artificial restrictions imposed on the finance commissions' scope of operations;(2) keep in view overall macroeconomic stability; (3) streamline management of government debt; (4) provide for appropriate incentives for inducing fiscal responsibility: (5) take a broader and integrated view of tax assignments; and (6) provide operational guidelines for the state level finance commissions. - Reproduced.
Keywords: Public finance - India; Public finance